The impact of Fresh Fruit Bunch (FFB) criteria towards the Oil Extraction Rate (OER) quality: a case study in Kluang Johor palm oil mills / Khairul Basri Akram Kamarudin - Kamarudin, Khairul Basri Akram (Faculty of Plantation and Agrotechnology, 2018)
Oil palm (Elaeis guineensis Jacq.) industry is one of the fastest growing sectors in Malaysia, where currently Malaysia is the one of the largest producer of palm oil in the world after Indonesia. The Crude Palm Oil (CPO) was extracted from Fresh Fruit Bunches (FFB) through the milling processes, and the percentage was also known as Oil Extraction Rate (OER). The OER was commonly used as the key factors in determining the performance of the producers. This study was conducted to determine the FFB grading in affecting the OER percentages by the mill. The research methodology which adopted for this study was based on the quantitative data analysis. The available historical data which are secondary data from the selected Palm Oil Mill in Johor was collected and analysed. This results showed that the fruit quality from the contributing estates were significantly affects the OER performance of the mill as ripe, dirty, empty and long stalk shows the p-value<0.01. There a positives relationship between ripe bunch towards OER and also negative relationship between empty, dirty and long stalk bunch. The study concluded that the low quality of FFB grading is the main factor that lead to the drop of OER percentage and also gave the greater impact to the performance of OER that being produced.